Illegal Cigarette Excise Crime in Gorontalo: Criminology and Law Enforcement Perspectives - Moh. Bayu Saputra; Suwitno Yutye Imran; Waode Mustika; Sajjad Hussain (Yayasan Cendekia Gagayunan Indonesia, 2026)
This study aims to analyze the criminological factors underlying illegal excise cigarette crimes, identify the transformation of perpetrators' modus operandi, and evaluate the effectiveness of law enforcement in Gorontalo Province. This research employs an empirical juridical method with socio-legal research and criminological legal research approaches, conducted as a case study at the Gorontalo Customs and Excise Supervisory Office. Primary data were obtained through semi-structured interviews with Customs investigators, while secondary data were derived from enforcement documentation for the period 2023–2025 as well as criminological literature and excise regulations. Data analysis was conducted qualitatively using a thematic analysis approach integrated with four classical criminological theories, namely Becker's Rational Choice Theory, Merton's Anomie Theory, Sutherland's Differential Association Theory, and Hirschi's Social Control Theory. The findings reveal a drastic increase in illegal cigarette discoveries in Gorontalo, from 133,000 sticks in 2023 to 878,000 sticks in 2025, driven by price disparity between legal and illegal cigarettes, socio-economic structural pressures, organized informal distribution networks, and the weak social bonds of perpetrators toward legal norms. This study finds that the distribution modus operandi of illegal cigarettes has undergone a significant transformation toward digital-logistics channels through the exploitation of e-commerce platforms and courier services with disguised cargo identities a phenomenon that has received limited scholarly attention in previous research. The contribution of this study lies in the application of a combinative approach integrating four classical criminological theories to analyze economic crime at the regional level, while simultaneously affirming the urgency of digital surveillance reform and excise intelligence strengthening as relevant policy responses within the national excise policy framework.